A design proposal for the implementation of a management system based on ISO 9001: 2008 for the Logistecsa company branch Guayaquil. - Casco López, María Gabriela; García Santana, Cristina Ramon; Lindao Quinde, Anggely Vanessa (Ingeniería Química y Desarrollo, 2024)
This  research work is aimed at optimizing and standardizing  processes and procedures Regional Logistics Operator Logistecsa specifically in its branch located north of the city of Guayaquil, to achieve this goal the design of a management system was conducted Quality based on ISO 9001: 2008. In the document the current situation of the organization is detailed, for which tools were used as Ishikawa diagram, Multivoting and Process Mapping, parallel to this a diagnosis is made ISO  9001: 2008 using Likert Scale, in which the level of implementation will qualify each of the sections. Surveys were conducted to internal and external customers, to check the level of satisfaction. Finally, the proposal is presented as the development of the quality manual for branch.
Keywords: Logistic; System; Management; Quality